Agenda Setting for Kampung KORPRI as a Model of Civic Dedication: Agenda Setting Kampung KORPRI sebagai Model Pengabdian Masyarakat - Akbar Wicaksono, Novan; Suradji Muhammad, Adji (Indonesian Journal of Innovation Studies, 2025)
General Background: Agenda setting is a vital phase in public policy development, determining which public issues are prioritized. Specific Background: The Kampung KORPRI program in Yogyakarta, initiated by the Dewan Pengurus KORPRI Kota Yogyakarta, represents a thematic social service activity in Karangkajen, not as a residential area for KORPRI members but as a locus for community service. Knowledge Gap: Despite its significance, there is limited research on how agenda setting shapes public service programs initiated by civil servant organizations without political motives. Aims: This study aims to analyze the agenda setting process in the formation of the Kampung KORPRI program through planning and formulation stages. Results: Using a descriptive qualitative method with an explorative approach, supported by in-depth interviews, observation, and documentation, findings show that planning was conducted by each involved unit based on specific activity targets, while formulation involved detailed design and confirmation of implementation. Novelty: The program is confirmed to be free from political agendas, evidenced by the absence of KORPRI members in the 2024 local elections. Implications: This research highlights the potential of neutral, community-oriented civil servant initiatives and emphasizes the importance of structured agenda setting in realizing sustainable public service programs. Highlights: Non-political civil servant program for community service. Focus on planning and formulation stages. Structured agenda setting ensures policy effectiveness. Keywords: Agenda Setting, Public Policy, Kampung KORPRI, Community Service, Yogyakarta